Examining the Effects of Social Media Engagement, Electronic Word of Mouth (e-WOM), Brand Image, and Purchase Intention in Online Service Industries - Luqman Abdulloh Mahmuda; Latifa Dinar Rahmani Hakim; Ana Fitriyatul Bilgies; Umi Nur Solikah (Malaqbi Publisher, 2026)
This study aims to examine the effects of social media engagement and electronic word-of-mouth (e-WOM) on purchase intention in online service industries, with brand image serving as a mediating variable. A quantitative research approach with a causal design was employed, and data were collected through an online survey from 240 respondents who actively use social media and online service platforms. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that social media engagement and e-WOM have significant positive effects on both brand image and purchase intention. Additionally, brand image has a strong positive influence on purchase intention and significantly mediates the relationships between social media engagement, e-WOM, and purchase intention. These findings highlight the critical role of digital interaction and online consumer communication in shaping brand perception and driving purchasing behavior. The study provides practical implications for businesses to enhance customer engagement, manage online reviews effectively, and strengthen brand image to increase consumer purchase intention in competitive digital markets.